Heavy metals phytofiltration potential of Hydrocotyle umbellata from Nullah Lai wastewater and its environmental risk. Issue 14 (6th December 2022) - Bokhari, Syeda Huma; Nawaz, Ghazala; Azizullah, Azizullah; Mahmood-Ul-Hassan, Muhammad; Ali, Zeshan
Abstract: This study aims to examine the heavy metal phytofiltration potential of Hydrocotyle umbellata from Nullah Lai wastewater and its environmental risk. Wastewater was initially analyzed for heavy metals and physicochemical parameters and compared with irrigation water standards. The phytofiltration potential of H. umbellata was determined by periodically monitoring heavy metal concentrations at time points T1 (day 05), T2 (day10), T3 (day 15), and T4 (day 20). This study shows that some water parameters reached the permissible limits after treatment with H. umbellata . Results of the risk analysis reveal a significant discharge (kg d −y ) of heavy metals to arable land. Phytofiltration efficiency of H. umbellata for water quality parameters was in order of Ni (98.75%), Cr (98.11%), Cd (95.84%), Pb (94.90%), Cu (94.10%), Zn (85.34%), BOD (53.67%), TDS (29.28%), EC (27.31%), Cl (6.65%), and SAR (6.34%). The growth of H. umbellata in wastewater resulted in heavy metal bioaccumulation in both roots and shoots of the plant. Less than 01 translocation factor (TF) values for cadmium, copper, lead, chromium, and zinc showed the metal tolerance ability of the tested plant. These results demonstrated that treated water could be used in water-deficient peri-urban areas as supplementary irrigation. Novelty Statement: This study evaluates the phytofiltration potential of Hydrocotyle umbellata for heavy metals (Cu, Cr, Cd, Pb, Ni, and Zn) from Nullah Lai wastewater by greenhouse experiments. The environmental risk associated with using Nullah Lai wastewater for irrigation purposes was estimated.